Medieval Reports of the Preservation and Looting of Pre-Islamic Burials in South Arabia. (1st March 2019) - Mahoney, Daniel
In the tenth century, the polymath Abu Muhammad al-Hamdani compiled a ten-volume compendium, entitled al-Iklı-l (The Crown), which narrates the history of South Arabia from the pre-Islamic to the early Islamic periods with the aim of extolling the various achievements and virtues of this region. The eighth volume of this compendium contains a collection of reports that describe the uncovering of pre-Islamic burials in the early Islamic period. Although the veracity of some reports may be questioned due to their inclusion of fantastical elements, these accounts portray a vivid imagining of the ancient tombs themselves and the stories of those buried within, as well as show the varied reactions to these sites. In some reports, the interred are revered and the chambers are returned to their former state. But in others, ambivalence is shown toward those buried, even when the inscriptions found at the site communicate that the interred testified to a belief in one god, and the tombs are looted. Overall, these rich reports do not merely depict encounters with pre-Islamic funerary remains, but also serve to connect South Arabia's past with major narratives and themes of Islamic history.